2021
DOI: 10.3390/biomedicines9010077
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Prefrontal Cortex–Thalamic Circuitry after Acoustic Trauma

Abstract: In the adult auditory system, loss of input resulting from peripheral deafferentation is well known to lead to plasticity in the central nervous system, manifested as reorganization of cortical maps and altered activity throughout the central auditory pathways. The auditory system also has strong afferent and efferent connections with cortico-limbic circuitry including the prefrontal cortex and the question arises whether this circuitry is also affected by loss of peripheral input. Recent studies in our labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 60 publications
3
4
1
Order By: Relevance
“…The present results regarding effects on SFRs in control animals are in broad agreement with previous studies in rats ( Barry et al, 2017 , 2021 ). Electrical stimulation of PFC resulted in either no effect, excitation or inhibition of MGN neuronal activity.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The present results regarding effects on SFRs in control animals are in broad agreement with previous studies in rats ( Barry et al, 2017 , 2021 ). Electrical stimulation of PFC resulted in either no effect, excitation or inhibition of MGN neuronal activity.…”
Section: Discussionsupporting
confidence: 93%
“…Electrical stimulation of PFC resulted in either no effect, excitation or inhibition of MGN neuronal activity. However, whereas in the present study more than half of the neurons showed no effect of PFC stimulation, in the studies of Barry et al (2017 , 2021) no effect was only seen in about 20% of neurons. It should be noted that neurons that did not exhibit an effect were found in the same tracks as neurons that displayed either excitation or inhibition, which demonstrates that the lack of effect did not occur as a result of incorrect electrode placement or due to low levels of current intensity.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations